(untitled) (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2021)
Shipbuilding nearly 2/3 of the work is welding work. There are several variations of the weld joint as an option based on the thickness and quality of the material, the method of welding. Welding results generally depend heavily on the skill of the welder. Weld damage both on the surface and on the inside is difficult to detect with a simple test method. In addition, because the structure being welded is an integral part of the entire body of the weld material, the cracks that arise will spread quickly and may even cause serious accidents. In general, welding on ships has requirements from the Classification Agency which supervises and provides the feasibility of the ship’s construction strength. To meet these requirements, the role of the welder and technique is very large, so that the ship gets good welding quality and can be accepted by the shipowner and the classification agency.